The Development of Contemporary Student Engagement Practices at the University of Winchester and Winchester Student Union, UK - Lowe, Tom; Shaw, Cassie; Sims, Stuart; King, Savannah; Paddison, Angus (International Journal for Students as Partners, 2017)
This case study explores practice in four areas of student engagement activity which were developed in partnership between the University of Winchester and Winchester Student Union. The development, motivations, stakeholders, and challenges of activities built around the principles of representation, change, feedback, and research are discussed. Relationships between practices will be explored in the context of a proposal for how discrete practices can complement one another to create a community of partnership. The case study focuses on four key initiatives: Student Academic Representatives, Student Fellows Scheme, Student-Led Teaching Awards, and the Winchester Research Apprenticeship Programme. The four key initiatives are contextualised with a discussion of an ongoing project that seeks to provide greater coherence to student engagement through an institution-wide movement towards embedding partnership.